Reconciling the Provisions of Islamic Sharia and the Principles of Civil Law in Regulating Private Relations - هويدي اسامة حسن; النيساني عبدالله عمر احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
For centuries, Islamic Sharia remained the sole reference framework for regulating private relations in Islamic societies, relying on a comprehensive system of jurisprudential rulings derived from the Holy Qur’an and the Prophetic Sunnah, along with the rigorous scholarly interpretations that stemmed from them. With the advent of legal modernization in the Islamic world—particularly following the influence of Western civil law systems in the wake of colonialism—the need arose to reconsider how private relations are regulated, in a way that reconciles religious authenticity with the demands of the modern age. Civil law, as one of the most prominent forms of codified legislation, seeks to regulate private relations between individuals based on principles of justice and equality, relying on abstract rules aimed at achieving social and economic stability. However, these rules often diverge from the provisions of Sharia, which are rooted in a distinct religious and ethical philosophy. This presents a fundamental challenge: how to reconcile the two systems without compromising the essence of either. Many Arab and Islamic countries have adopted hybrid legal models, drawing inspiration from Islamic Sharia in certain areas while relying on civil law in others, in an effort to strike a balance between religious reference and contemporary legal reality. While countries such as Saudi Arabia and Yemen have adopted Sharia as the sole and primary source of legislation, others like Jordan and Egypt have codified Sharia provisions within the framework of civil law, benefiting from the Western experience in drafting legal rules. Manifestations of reconciliation between the two systems are evident in several domains, most notably contracts, property, and civil liability. Islamic jurisprudence had already developed precise rules for regulating these relations, such as the principle “contracts are the law of the contracting parties,” the rule “harm must be eliminated,” and the maxim “liability accompanies benefit.” Arab legislators drew upon these principles and incorporated them into civil law texts, with modifications suited to the modern legal context. Reconciling Islamic Sharia provisions with civil law principles is not merely a process of merging texts; it is a profound intellectual endeavor that requires a deep understanding of the spirit of both systems, and a grasp of the objectives of Sharia and the principles of codified justice. Hence, the importance of this research lies in shedding light on the mechanisms of reconciliation, identifying points of harmony and divergence, and proposing practical approaches to achieving legislative integration that preserves Islamic identity while keeping pace with contemporary developments.